Language Revitalization through Education and Tourism Industry in West Java, Indonesia - Lilies Setiasih (Universitas Islam Bandung, 2014)
Culture is the system of knowledge shared by a relatively large group of people. It is classified into three categories; ideas, behavior,a nd products which are shared by members of a given group. Language as one aspect of behavior (Robinson, 1988: 7) is a valuable resource and a contributing factor towards the sustainable development of the people speaking the language. The role of a language, for instance, in society is significant as a vehicle for the exchange of information and facilitating the transmission of knowledge. It is an indelible expression of life that conveys core values, builds ambition and spurns invention essential to strengthening the aspiration of the people. Language as part of culture and heritage stimulates the generation of ideas vital to the creation of a strong social infrastructure. Revitalizing a language is a component critical to strengthening an ethnic minority community on the margins of society who struggle to retain its identity. Sundanese language (bahasa Sunda) is one of the ethnic languages in Indonesia which is challenged by the existence of traditional, national, and foreign values merged in one community so that it faces the declination of speakers that limits its opportunity for having high position and vitality. Tourism industry and education are two of alternative media to revitalize the language which will be discussed in this paper.